GLOBAL RESEARCH LANDSCAPE ON FAST FOOD CONSUMPTION AND ITS HEALTH IMPACTS: A BIBLIOMETRIC ANALYSIS AND VISUALISATION OF RESEARCH TRENDS AND THEMES - Prajitha V V; Dr Vipin Chandran K P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Fast food consumption, characterized by the intake of calorie-dense and nutrient-poor meals, poses significant health risks, including obesity, chronic diseases, and mental health issues. This bibliometric analysis examines the research landscape on fast food consumption and its health impacts using data retrieved from the Scopus database, analyzing 545 publications spanning 1989 to 2023. Tools such as Biblioshiny and VOSviewer were employed to explore annual scientific production, identify prolific authors and key sources, and map the relationships between authors, sources, and countries using a three-field plot. The findings indicate a steady increase in research output, with the highest growth observed in the last decade, reflecting rising global concern. Trend analysis reveals a shift from foundational topics like obesity and BMI to emerging themes such as COVID-19, mental health, and food environments. The thematic map categorizes research into foundational, motor, niche, and emerging themes, highlighting key areas driving innovation and identifying underexplored topics. Bibliographic coupling analysis underscores the influence of foundational works while revealing integration opportunities for emerging studies. The co-occurrence network of keywords highlights the interdisciplinary nature of this research, spanning public health, behavioral science, and nutrition. Global collaboration patterns, led by the United States, reveal strong international partnerships but emphasize the need for enhanced regional efforts. This study provides insights into the evolving research priorities and underscores the necessity of interdisciplinary approaches to mitigate the health risks associated with fast food consumption.